Academic-community solidarities in land occupation as an Indigenous claim to health: culturally centered solidarity through voice infrastructures - Elers, Christine; Dutta, Mohan (Frontiers in Communication, 2023)
In this work, we explore the role of land in Indigenous theorizing about health, embodied in a land occupation that resisted a climate-adaptive development project imposed on the community from the top down by the local government. The proposed development project of building a stop bank on the Oroua River sought to alienate Māori from the remnants of the land. Embedded in and emerging from a culture-centered academic-community-activist partnership, an advisory group of Māori community members om the “margins of the margins” came together to participate in the occupation of the land to claim it as the basis for securing their health. This study describes the occupation and the role of our academic-activist intervention in it, theorizing land occupation as the root of decolonizing health emerging from Indigenous struggles for sovereignty (Tino rangatiratanga). The community advisory group members brought together in a culture-centered intervention, collaborated in partnership with the academic team, generated video narratives that resisted and dismantled the communicative inversions produced by the settler colonial state to perpetuate its extractive interests and produced communicative resources that supported the land occupation led by the broader Whānau. This study concludes by arguing that the culture-centered approach offers a meta-theory for decolonizing health communication by building voice infrastructures that support Indigenous land struggles.